NIR‐II Excitation Phototheranostic Nanomedicine for Fluorescence/Photoacoustic Tumor Imaging and Targeted Photothermal‐Photonic Thermodynamic Therapy - Dai, Yeneng; Zhao, Honghai; He, Kun; Du, Wenyu; Kong, Yingjie; Wang, Zhen; Li, Meixing; Shen, Qingming; Sun, Pengfei; Fan, Quli (Small (Weinheim an der Bergstrasse, Germany), 2021)
The success of phototheranostics is hampered by some intrinsic defects, such as limited light penetration depth, heat resistance of tumor cells to photothermal therapy (PTT) induced by heat shock protein (HSP) and stress resistance against photodynamic therapy (PDT) caused by hypoxia microenvironment of tumor. Herein, a second near infrared (NIR‐II) light excitation phototheranostic nanomedicine has been fabricated by integrating the semiconducting polymer, azo compound, and HSP inhibitor into a thermosensitive liposome, followed by modification with targeting aptamer, forming Lip(PTQ/GA/AIPH) for multimodal phototheranostics of triple‐negative breast cancer (TNBC). The phototheranostic nanomedicine provides tumor targeting NIR‐II fluorescence and photoacoustic dual‐modal imaging, as well as NIR‐II PTT. The released HSP inhibitor can effectively inhibit the activity of HSP for enhanced NIR‐II PTT. Moreover, azo compound can be decomposed by the NIR‐II photothermal activation, generating cytotoxic free radicals and realizing oxygen‐irrelevant photonic thermodynamic therapy (PTDT) effects. Under the NIR‐II laser irradiation, NIR‐II fluorescence/photoacoustic dual‐modal imaging guided enhanced NIR‐II PTT and PTDT by Lip(PTQ/GA/AIPH), can achieve precise diagnosis and effective suppression of deep‐seated TNBC with negligible side effects. This work develops a promising NIR‐II excitation phototheranostic nanomedicine for spatiotemporally specific diagnosis and combination therapy of TNBC. Novel second near infrared (NIR‐II) light excitation phototheranostic nanomedicine was constructed by coencapsulating semiconducting polymer, heat shock protein (HSP) inhibitor, and azo compound into aptamer AS1411 modified liposomes. Such nanomedicine displays an encouraging therapeutic effect for tumor, benefiting from the NIR‐II FI/PAI dual‐modal imaging guided and enhanced photothermal‐photonic thermodynamic therapy, triggered by single NIR‐II laser.